Assessment of nucleic acid modification induced by amotosalen and ultraviolet A light treatment of platelets and plasma using real‐time polymerase chain reaction amplification of variable length fragments of mitochondrial DNA. Issue 2 (7th October 2015) - Bakkour, Sonia; Chafets, Daniel M.; Wen, Li; Dupuis, Kent; Castro, Grace; Green, Jennifer M.; Stassinopoulos, Adonis; Busch, Michael P.; Lee, Tzong‐Hae
Abstract : BACKGROUND: Pathogen inactivation methods are increasingly used to reduce the risk of infections after transfusion of blood products. Photochemical treatment (PCT) of platelets (PLTs) and plasma with amotosalen and ultraviolet A (UVA) light inactivates pathogens and white blood cells through formation of adducts between amotosalen and nucleic acid that block replication, transcription, and translation. The same adducts block the amplification of nucleic acids using polymerase chain reaction (PCR) in a manner that correlates with the number of adducts formed, providing a direct quality control (QC). Current QC measures for PCT rely on indirect methods that measure the delivered UVA dose or percent residual amotosalen after illumination, rather than directly measuring nucleic acid modification. STUDY DESIGN AND METHODS: Endogenous mitochondrial DNA (mtDNA), which is detectable in PLT and plasma units, was chosen as a target for the quantification of photochemically induced modifications. DNA was extracted from untreated or amotosalen and UVA–treated PLTs or plasma, and mtDNA fragments of variable lengths were quantified using a real‐time PCR inhibition assay. RESULTS: PCT induced increasing real‐time PCR inhibition of mtDNA amplification for larger amplicon sizes. Amplification was unaffected by treatment with amotosalen or UVA alone, whereas up to 3 log inhibition was observed after PCT. Blinded PCR testing of a panel of 110 samples each, from PLT or plasma components prepared for routine use within a blood center, allowed 100% discrimination between untreated and treated units. CONCLUSION: Our initial findings indicate that an adequately sensitive, quantitative real‐time PCR inhibition assay targeting mtDNA could provide a valuable tool to confirm and monitor PCT.